Attitude towards ageing and perceived health status among the elderly in Malaysia - Mohamad Yunus, Noor'ain; Abb Manaf, Noor Hazilah; Omar, Azura; Juhdi, Nurita; Omar, Mohd Azhadi; Salleh, Mohmad (Faculty of Business and Management, Universiti Teknologi MARA, 2016)
There is an increasing number of older people globally, thus it is essential to build knowledge of how older people view their own ageing, considering their health related circumstances. However, limited attention has been given to attitude towards ageing, particularly in Malaysia. The purpose of this study is to examine the relationship between selfperception of ageing and perceived health status in adults aged 60 years and above. This study is primarily conducted via survey among the elderly patients who are 60 years old and above, who are using the services at public hospitals in Peninsular Malaysia. The ‘Attitudes towards ageing’ questionnaire was used to measure participants’ perception of ageing, while perceived health status was measured using questions from the Study of Global Ageing and Adult Health (SAGE) developed by World Health Organization(WHO). All items in both questionnaires were measured on a 5-point Likert-scale. The findings reveal that positive attitudes to ageing were associated with health status in older adults. The research contributes to greater understanding of the attitudes among the elderly towards ageing and their perceived health status. Understanding these associations may help healthcare providers and policy makers consider strategies to enhance the quality of life of the elderly.